Circles of Deceit - Bawden N. Nina (London, Virago Press, 2000)
Circles of Deceit is narrated by a painter who specialises as a copyist, this is his story: 'bothered by bills and artistic conscience in about equal measure. . .susceptible to, bullied and badgered by women.' Major figures on the canvas are Clio, his child-bride; Helen, his first wife; his mother Maisie. They confound lies and the truth in a subtle weave, while the silent agony of the painter's son is a poignant reflection on the busy web of deception. And as the copyist transcribes his modern versions of Old Masters, so the past keeps breaking through the surface of the present, until fact and fiction like art and life, meet in a remarkable conclusion.